2016
DOI: 10.18632/oncotarget.14328
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of tanshinone IIA against cardiac hypertrophy in spontaneously hypertensive rats through inhibiting the Cys-C/Wnt signaling pathway

Abstract: The study aimed to investigate the protective effect of tanshinone IIA against cardiac hypertrophy in spontaneously hypertensive rats (SHRs) through the Cys-C/Wnt signaling pathway. Thirty SHRs were randomly divided into cardiac hypertrophy, low- and high-dose tanshinone IIA groups. Ten Wistar-Kyoto rats were selected as control group. The systolic blood pressure (SBP), heart weight (HW), left ventricular weight (LVW) and body weight (BW) of all rats were recorded. HE staining and qRT-PCR were applied to obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 37 publications
0
19
0
2
Order By: Relevance
“…The enhancement effects of Tan IIA on the antitumor activity of Dox in vitro led us to investigate whether this effect would be maintained in vivo, and meanwhile, we also investigate the effect of Tan IIA on the toxic side effects of Dox. Because Tan IIA had antitumor activity in addition to its cardiovascular protective effect, and one of the main toxic side effects of Dox was cardiotoxicity, and thus, we selected Tan IIA at the concentration of 10 mg/kg as commonly used for cardiovascular protection studies (Feng, Chen, Pi, Wang, & Zhan, ; Yuan, Jing, Wu, Chen, & Fang, ) to better evaluate the effect of Tan IIA on the cytotoxicity of Dox. As expected, both Tan IIA and Dox had certain inhibitory effect on the xenograft tumor growth of MCF‐7 cells in nude mice.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The enhancement effects of Tan IIA on the antitumor activity of Dox in vitro led us to investigate whether this effect would be maintained in vivo, and meanwhile, we also investigate the effect of Tan IIA on the toxic side effects of Dox. Because Tan IIA had antitumor activity in addition to its cardiovascular protective effect, and one of the main toxic side effects of Dox was cardiotoxicity, and thus, we selected Tan IIA at the concentration of 10 mg/kg as commonly used for cardiovascular protection studies (Feng, Chen, Pi, Wang, & Zhan, ; Yuan, Jing, Wu, Chen, & Fang, ) to better evaluate the effect of Tan IIA on the cytotoxicity of Dox. As expected, both Tan IIA and Dox had certain inhibitory effect on the xenograft tumor growth of MCF‐7 cells in nude mice.…”
Section: Resultsmentioning
confidence: 99%
“…The results showed that although PTEN inhibition reduced the inhibitory effect of Tan IIA on AKT activation but had no significant effect on the effect of Tan IIA downregulating the expression of efflux ABC transporter proteins including P-gp, BCRP and MRP1 (Figure 5).3.6 | In vivo, Tan IIA enhances chemotherapeutic effect of Dox against human breast cancer while reducing its toxic side effectsThe enhancement effects of Tan IIA on the antitumor activity of Dox in vitro led us to investigate whether this effect would be maintained in vivo, and meanwhile, we also investigate the effect of Tan IIA on the toxic side effects of Dox. Because Tan IIA had antitumor activity in addition to its cardiovascular protective effect, and one of the main toxic side effects of Dox was cardiotoxicity, and thus, we selected Tan IIA at the concentration of 10 mg/kg as commonly used for cardiovascular protection studies(Feng, Chen, Pi, Wang, & Zhan, 2017;Yuan, Jing, Wu, Chen, & Fang, 2014) to better evaluate the effect of Tan IIA on the cytotoxicity of Dox.As expected, both Tan IIA and Dox had certain inhibitory effect on the xenograft tumor growth of MCF-7 cells in nude mice. However, when Dox was combined with Tan IIA, the inhibitory effect was significantly enhanced(Figure 6a).…”
mentioning
confidence: 99%
“…The anti-hypertrophic properties of tanshinone IIa have been observed in spontaneously hypertensive rats [218,219] , two-kidney one-clip hypertensive rats [220] , two-kidney two-clip hypertensive rats [221] , angiotensin II-infused rats [222] , and pressureoverloaded rats induced by transverse aortic constriction [223] . In most of these studies, favorable effects of tanshinone IIa have reflected the decrease in the ratio of left ventricular weight to body weight, and the decrease in cardiomyocyte size and diameter are independent of the alteration of systemic blood pressure [218,[220][221][222] , thus eliminating the possibility that tanshinone IIa modulates cardiac hypertrophy by lowering blood pressure.…”
Section: Protective Effects Of Tanshinone Iia Against Pathological Camentioning
confidence: 99%
“…Tanshinone IIa represses the hypertrophic process in response to hypertrophic stimuli, including angiotensin II [222,225,226] , isoproterenol (ISO) [227] , and insulin-like factor-II (IGF-II) [228] , suggesting a broad anti-hypertrophic effect of tanshinone IIa. The regulation of tanshinone IIa in cardiomyocyte hypertrophy involves multiple mechanisms: (1) tanshinone IIa suppresses intracellular signaling pathways that regulate expression of the cardiac genes encoding structural proteins or regulatory proteins, including MEK/ERK [222] , AP1 (c-jun/c-fos) [225,226] , calcineurin/ NFAT3 (nuclear factor of activated T cells 3) [227,228] , and the Cys-C/Wnt signaling pathway [219] ; (2) tanshinone IIa upregulates eNOS expression and promotes the phosphorylation of eNOS in the myocardium [187,219] ; (3) tanshinone IIa activates silent information regulator 1 (SIRT1) to attenuate oxidative stress and inflammation involved in cardiac hypertrophy [223] ; (4) tanshinone IIa diminishes NADPH oxidase-derived oxidative stress [221] . The anti-fibrotic effects of tanshinone IIa involve inhibition of myofibroblast proliferation [229] ; prevention of the deposition of extracellular matrix (ECM) components, such as collagen and fibronectin [230][231][232][233][234] ; and regulation of the balance between MMPs and tissue inhibitor of metalloproteinases (TIMPs) [220,232,235,236] .…”
Section: Protective Effects Of Tanshinone Iia Against Pathological Camentioning
confidence: 99%
“…The canonical Wnt signaling primarily promotes β-catenin-mediated activation of transcription, while the non-canonical Wnt signaling involves a calcium-dependent protein kinase C-mediated Wnt/Ca 2+ pathway and a dishevelled-dependent c-Jun N-terminal kinase-mediated planar cell polarity pathway [ 8 , 9 ]. Although both canonical and non-canonical Wnts have been implicated in various cardiac responses to physiological and pathological stimuli [ 10 , 11 ], canonical Wnt signaling plays dominant roles in the myocardial regeneration, specification, morphogenesis and differentiation [ 9 , 12 ]. It has been showed that blocking of Wnt3a-associated signaling could prevent the development of heart failure after MI [ 13 ].…”
Section: Introductionmentioning
confidence: 99%